BUILDING FAITH AND WEALTH: ECONOMIC OPPORTUNITIES ARISING FROM RAM MANDIR - Samdish Sharma, Dr. M.R Behera , (Chelonian Research Foundation, 2024)
This paper explores the intricate relationship between religious development and socioeconomic growth in the context of the Ram Mandir project in Ayodhya, Uttar Pradesh. Utilizing data collected from 500 respondents within the local community, this study investigates the perceived economic opportunities and the potential for wealth generation stemming from the temple’s construction and its subsequent role as a pilgrimage site. The findings reveal a strong correlation between faith-based tourism and economic upliftment, with respondents highlighting various avenues for income generation, including hospitality services, local crafts, retail, and transportation. The research illustrates that the Ram Mandir not only serves as a spiritual symbol for millions but also as a catalyst for economic revitalization in Ayodhya. Respondents expressed optimism regarding job creation and the inflow of tourists, which is expected to bolster local businesses and enhance overall community development. Furthermore, the paper delves into the role of community engagement, with local stakeholders actively participating in planning discussions to ensure that the economic benefits of the temple’s establishment are equitably distributed. By employing a qualitative interviews, this paper provides a comprehensive overview of local perceptions regarding the Ram Mandir’s impact on economic growth. The results underscore the significance of integrating religious and economic initiatives to foster sustainable development in culturally rich areas. Ultimately, this study contributes to the broader discourse on faith and economy, illustrating how spiritual landmarks can generate substantial economic opportunities while simultaneously reinforcing community identity and heritage.